Mielites infecciosas: características clínico-epidemiológicas de série de casos em Belém – Pará, no período de janeiro de 1998 a julho de 2010 - LISBOA NETO, Carlos dos Reis (2023)
A retrospective study was performed to describe the clinical and epidemiological profile of patients with suspected infectious myelitis admitded at João de Barros Barreto Hospital and Ofir Loyola Hospital, from January 1998 to July 2010. Thirteen patients aged seven to 53 years, seven men and six women, most coming from the interior of the state. Ten evolved acute (76.9%) and three insidious (23%). All had a history of fever, 77% dorsalgia and 23% adenopathy. As for the motor deficit, seven (53.8%) had paraplegia, five (38.4%) paraparesis and one (7.6%) quadriparesis. Sensory changes were described in all patients and sphincter in 12 (92.3%). Six (46.1%) had spinal MRI with T2 hyperintensity and two with intermediate signal on T1.Three (23%) had CSF examination with inflammatory pattern. Serologic tests were performed in nine patients (69.2%), which results were positive in four (30.7%) to agents such as HIV, HTLV, cytomegalovirus and toxoplasma. Two other cases (15.3%) were in the presence of dengue and varicella. Six patients were underwent to specific treatment and length of hospitalization ranged from 10 to 106 days (mean 38.9 days), with 12 hospital discharges for medical management and one death. During hospitalization there was no neurological recovery, with partial improvement in five patients (38.4%). The definitive diagnosis was hampered by the absence in the hospitals studied for own MRI and by not carrying enough of exams or solicitation for the etiological investigation.